PROFITABILITAS, KERAGAMAN GENDER, MANAGERIAL AGENCY COTS, DAN KAPASITAS OPERASI TERHADAP FINANCIAL DISTRESS - Kartika Sari, Fitry; Maharani, Rieska (UMSurabaya Publishing, 2024)
ABSTRACT The existence of Covid-19 had also affected the decline in activities and income of various business sectors. If the decrease in income occurred continuously, it was feared that it can cause financial distress and even bankruptcy. The purpose of research determined the Effect of Profitability, Gender Diversity, Managerial Agency Costs, and Operating Capacity on Financial Distress in Infrastructure, Utilities, and Transportation Sector Companies Listed on the Indonesia Stock Exchange for the 2018-2022 period. This study uses a quantitative approach. Data processing techniques using SPSS 16.0 for Windows were tested using multiple linear regression analysis method. The sampling technique used purposive sampling method in order to obtain a sample of 90 companies. The results show that partially (1) Profitability has a positive and significant effect on financial distress. (2) Gender Diversity had a positive and significant influence on financial distress. (3) Managerial agency costs had a positive and significant impact on financial distress. (4) Operating Capacity had a positive and significant impact on financial distress. While simultaneously Profitability, Gender Diversity, Managerial Agency Costs, and Operating Capacity had an influence on financial distress with an adjusted R square value of 34.2%.